stiind ca a=100-(8*2+7*8) b=(9*8+7*6)-120 c=6+3*6-20
calculeaza a-b-c=
a+2*(b+c)=
a+3*b+c
Răspunsuri la întrebare
Răspuns de
0
A=100-(8•2+7•8)=100-(16+56)=100-72=28
B=(72+42)-120=114-120=-6
C=6+18-20=24-20=4
a-b-c=28-(-6)-4=28+6-4=34-4=30
a+2•(b+c)=28+2•(-6+4)=28+2•(-10)=28-20=8
a+3•b+c=28+3•(-6)+4=28-18+4=14
B=(72+42)-120=114-120=-6
C=6+18-20=24-20=4
a-b-c=28-(-6)-4=28+6-4=34-4=30
a+2•(b+c)=28+2•(-6+4)=28+2•(-10)=28-20=8
a+3•b+c=28+3•(-6)+4=28-18+4=14
rrobi:
multumesc
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Biologie,
9 ani în urmă
Istorie,
9 ani în urmă
Limba română,
9 ani în urmă